Using Assessment for Effective Learning - Sangai, Sandhya (THE PRIMARY TEACHER, 2019)
Improving the quality of elementary education was one of the thrust areas under SSA Phase II. Assessment that supports student learning will do a lot of good in achieving the goal of enhanced learning achievement by children in elementary schools. In the context of student learning, assessment is considered as the process of collecting and recording information to reflect how well a student is learning. There have been several efforts in this direction. The major ones at the national level are the development of the Continuous and Comprehensive Evaluation (CCE) package at the Primary and Upper Primary Levels, the formulation of learning outcomes for every class, and the development of CCE Guidelines up to the Elementary Level. In an educational context, we talk of three types of assessment — assessment for learning (formative assessment), assessment of learning (summative assessment), and assessment as learning (self-assessment). When the purpose of assessment is primarily to improve learning by children, and teachers adjust their teaching-learning styles and pedagogy, it is generally understood as ‘formative assessment’ or ‘assessment for learning’. When the work of the children is evaluated to declare what they learned in a specific period, the activity is described as ‘a summative assessment or ‘assessment of learning’. However, when children are motivated and they are involved in assessing their learning as well as learning by their peers, this kind of assessment is called ‘self-assessment’ or ‘assessment as learning’. This article discusses how to use technology to make these assessments useful, effective, and relevant.